Analysis of Hospital Readiness to Face the 'Smart Hospital' Era - Asti Nurhayati; Retno Tri Utami; Aslam Adzkia Al Qudsi (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2023)
Introduction : Smart hospital is an emerging and fast-developing innovation in the context of a rapid increase of internet users, an increasing demand for high-quality medical resources, and an aging population worldwide. It generally involves the use of the optimized and automated processes built on an information and communications technology (ICT) environment, especially based on the Internet of things (IoT), to offer assessment, consultation, direct treatment, services, and integrated care. This innovation has the potential and has already gained initial evidence to improve healthcare access, efficiency, or even effectiveness. Yet, along with these positive impacts and promises, a number of issues and challenges also appear.Methods: Study This is study quantitative with design survey research. Study This done on the month of June 2023. Instruments used in study This use questionnaire with the HOT-Fit method consisting of the 47 questions divided in 6 groups question namely: Human, Organization, Technology, Knowledge Users Regulations and Benefits. Subject for this study is hospital managers, administration staff and health workers. Data analysis using analysis multivariate .Result: 22 hospital state that digitization service health to a very smart hospital important one of them is applied For increase quality service House hurts and improves satisfaction patient. In application of smart hospital Sick need integrate between technology, service and regulation.Conclusion : Smart hospitals can influence health and medical policies and create new medical values by defining and quantitatively measuring detailed indicators based on data collected from existing hospitals. Simultaneously, appropriate government incentives, consolidated interdisciplinary research, and active participation by industry are required to foster and facilitate smart hospitals. Keywords: ,